Heating ability of magnetic nanoparticles with cubic and combined anisotropy - Usov, Nikolai A.; Nesmeyanov, Mikhail S.; Gubanova, Elizaveta M.; Epshtein, Natalia B. (Beilstein Journal of Nanotechnology, 2019)
The low frequency hysteresis loops and specific absorption rate (SAR) of assemblies of magnetite nanoparticles with cubic anisotropy are calculated in the diameter range of D = 20–60 nm taking into account both thermal fluctuations of the particle magnetic moments and strong magneto–dipole interaction in assemblies of fractal-like clusters of nanoparticles. Similar calculations are also performed for assemblies of slightly elongated magnetite nanoparticles having combined magnetic anisotropy. A substantial dependence of the SAR on the nanoparticle diameter is obtained for all cases investigated. Due to the influence of the magneto–dipole interaction, the SAR of fractal clusters of nanoparticles decreases considerably in comparison with that for weakly interacting nanoparticles. However, the ability of magnetic nanoparticle assemblies to generate heat can be improved if the nanoparticles are covered by nonmagnetic shells of appreciable thickness.
Keywords: fractal clusters; magnetite nanoparticles; magneto–dipole interaction; numerical simulation; specific absorption rate